Flood Rescue Boat as One of the Alternatives in Indonesia Waterways - Meitha Soetardjo; Ede Mehta Wardhana; Ahmad Bisri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2019)
Flooding is the most frequent disaster that hit Indonesia, especially in big cities with poor urban planning. Infrastructure damage has occurred, the fatalities which are likely to occur, both during floods and after floods. So far, the fatalities caused by floods are very difficult to control and even tend to increase. This condition is getting worse with the lack of facilities that support the evacuation process of flood victims. The aim of the study was to design a lifeboat that was able to evacuate flood victims and be able to overcome other problems that might arise when the evacuation process runs more efficiently. By collecting data from several agencies related to flood mitigation problems, interviews with experts, as well as several other references, it is hoped that relevant data can be collected, which can provide solutions to the problems faced. The stages of the research included the creation of concepts and the design of a hull shape that was adjusted for a flood rescue boat, a boat with high stability. By using of the Maxsurf V.8.5 and Hydromax V.8.5 program, it is expected that the design process and calculation of boat stability can be done more quickly and accurately. The results of research for several areas affected by floods, the existence of a rescue boat as a means to evacuate victims is urgently needed. So that the provision of a multifunctional flood rescue boat is the perfect solution to overcome this problem. To carry out this function, the stability of the rescue boat flood is one of the factors that must be considered so that the evacuation process can be carried out safely